PENGARUH ZAKAT, INFAQ DAN SHODAQOH TERHADAP LABA PADA PERBANKAN SYARIAH INDONESIA - Yohani Yohani; M. Yusuf (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2014)
The aim of this research is to get an empirical evidence about the impact of Zakat, Infaq dan Shodaqoh on profitability of Sharia Banking in Indonesia. The samples are colected by using purposive sampling method. The samples of this research are Sharia Banking in Indonesia during period Dec 2010- June 2014. Data collected through secondary data observation method. Analysis Method that is used in this research is simple linier regression. The result of this research shows that Zakat, Infaq dan Shodaqoh (ZIS) has significant effect on profitability of Sharia Banking. The amount of R2 in this research is 0,204. This result indicates that the effect of independent variable, Zakat, Infaq dan Shodaqoh to dependent variable, profitability of Sharia Banking can be explained by this model amount 20,4 %, while the remaining 79,6 % is influenced by other factors out of this research